2009
DOI: 10.1002/ace.321
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the literacy skills of adult immigrants and adult English language learners

Abstract: Most adults who are new to English manage to find work, raise children, and act as informed community members and citizens (Castro and Wiley, 2008). However, proficiency in English, particularly the ability to read and write the kind of English that educated adults use, goes hand in hand with access to a much broader range of information and affords a wider set of opportunities, particularly economic opportunities. Millions of the foreignborn come to the United States to find work and are a substantial and gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…When Latin American immigrants are able to enrol in such programs, long waiting lists, difficulties in transportation to and from classes and myriad work and family demands on immigrants' time make participation difficult (Wrigley, Chen, White, & Soroui, 2009). For all of these reasons, adult literacy and ESL services are essential, and existent programs are often in need of reform.…”
Section: Downloaded By [Mcmaster University] At 11:13 14 October 2014mentioning
confidence: 99%
“…When Latin American immigrants are able to enrol in such programs, long waiting lists, difficulties in transportation to and from classes and myriad work and family demands on immigrants' time make participation difficult (Wrigley, Chen, White, & Soroui, 2009). For all of these reasons, adult literacy and ESL services are essential, and existent programs are often in need of reform.…”
Section: Downloaded By [Mcmaster University] At 11:13 14 October 2014mentioning
confidence: 99%
“…Community‐based programs attract a diverse range of ELLs; depending on the program location, student profiles may include refugees, new arrivals, long‐term residents, lawful permanent residents, unauthorized immigrants, or immigrant youth (age 17–24) who have a variety of educational, cultural, and linguistic backgrounds (Center for Applied Linguistics, ). These populations all bring varied levels of English language proficiency and literacy (Wrigley, Chen, White, & Soroui, ). Student dropout rates can be high and proficiency gain rates low in these programs, with some 20% of learners attending less than 12 hours of instruction (Schalge & Soga, ) and reports of only 40% of participants across the nation advancing in proficiency each year (Kennedy & Walters, ).…”
Section: Faith‐based Esl Program Characteristics In the United Statesmentioning
confidence: 99%
“…This could be because employers admit that they assume having a name that doesn't sound English means that the potential employee has poor communication skills, so they do not even bother asking them for an interview (Oreopoulos and Dechief 2011). When they do obtain employment, Spruck-Wrigley et al (2009) found a 46% wage differential between immigrants who speak English fluently and those who do not. This puts immigrant women at a disadvantage because they typically lack the time and energy to learn English once in Canada because they have the double burden of paid and unpaid employment (Boyd 1984;Stewart 2006).…”
Section: Human Capitalmentioning
confidence: 99%